2019
DOI: 10.1111/aogs.13580
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of misoprostol vaginal insert compared with oral misoprostol in the induction of labor of nulliparous women: A randomized national multicenter trial

Abstract: Introduction Our objective was to compare the efficacy of a 200‐μg misoprostol vaginal insert vs oral misoprostol regarding the cesarean section rate and the time interval to vaginal delivery in nulliparous women with unfavorable cervix. Material and methods In this prospective multicenter trial, 283 nulliparous women at term with Bishop score <6 were randomized to induction of labor with either a misoprostol vaginal insert (n = 140) or oral misoprostol (n = 143). In the oral misoprostol group, a 50‐μg dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
3
11
0
4
Order By: Relevance
“…This was not in consistence with finding by many studies. [23][24][25] While Mahajan study in 2018 had the same finding as the current study. 18 This could be explained as well as expected as different dosage regimen between these studies and this study.…”
Section: Discussionsupporting
confidence: 81%
“…This was not in consistence with finding by many studies. [23][24][25] While Mahajan study in 2018 had the same finding as the current study. 18 This could be explained as well as expected as different dosage regimen between these studies and this study.…”
Section: Discussionsupporting
confidence: 81%
“…However, compared to other means of induction of labor, increased rates of tachysystole with misoprostol vaginal inserts (MVI) have been reported by several authors. [2][3][4] Presence of tachysystole during induction of labor is a concern as it is feared to lead to fetal blood deoxygenation due to decreased placental perfusion. 5 This in turn could lead to non-reassuring fetal heart traces, fetal acidosis, and hence higher rates of medical intervention and poorer neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…5 Despite the high frequency of tachysystole after induction of labor with MVI, no difference in cesarean section rate or neonatal outcome has been observed between MVI and other induction methods. [2][3][4] Currently, there is conflicting evidence regarding the clinical impact of tachysystole, as some authors have reported an increase in cesarean section rates, operative vaginal delivery and neonatal morbidity [6][7][8] while others found no significant differences. [9][10][11] More information is therefore needed on the association between tachysystole and progression to cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandins have been proven to induce labor whilst not increasing the rate of cesarean sections (CS) among women with unscarred uterus [7]. [8][9][10][11][12][13] even for women with an unfavourable cervix as to BISHOP scores [14], while reducing the need for oxytocin compared to dinoprostone vaginal insert or oral misoprostol [8,10,15].…”
Section: Resultsmentioning
confidence: 99%
“…Hyperstimulation syndrome requiring tocolysis is more common in women receiving MVI [8,10,11,14,16].…”
Section: Resultsmentioning
confidence: 99%